Perlindungan Hukum Terhadap Korban Trafficking di Indonesia: Perspektif Hak Asasi Manusia dan Undang-Undang Nomor 21 Tahun 2007 - Santosa, Tirsa Shany Anak (UM Purwokerto Press, 2024)
Human trafficking is still a major threat in Indonesia. Human trafficking is a cruel and sad phenomenon, especially as those who are trafficked are women and children. Sexual exploitation, coercion, fraud, forced labor, and abuse of power for the perpetrator's monetary gain or personal satisfaction are examples of trafficking victims. Human dignity and rights have been violated in this case. Human trafficking is a serious and cruel crime, which can cause physical, psychological and emotional suffering for victims. Victims of human trafficking crimes are not given much attention, this could be due to the focus on punishment being only given to the perpetrators which then signals the resolution of the problem. Therefore, there is a need for adequate legal protection to guarantee human rights.